The criticality of growth, urbanization, electricity and fossil fuel consumption to environment sustainability in Africa - Simplice Asongu; Mary O. Agboola; Andrew A. Alola; Festus Victor Bekun (African Governance and Development Institute (AGDI), 2019)
While most African economies are primarily sandwiched with the seemingly unsurmountable task of attaining consistent economic growth and unhindered energy supply, the enormous threat posed by environmental degradation has further complicated the economic and environmental sustainability drive. In this context, the present study examines the effect of economic growth, urbanization, electricity consumption, fossil fuel energy consumption, and total natural resources rent on pollutant emissions in Africa over the period 1980-2014. By employing selected African countries, the current study relies on the Kao and Pedroni cointegration tests to cointegration analysis, the Pesaran's Panel Pooled Mean Group-Autoregressive distributive lag methodology (ARDL-PMG) for long run regression while Dumitrescu and Hurlin (2012) is employed for the detection of causality direction among the outlined variables. The study traces long run equilibrium relationships b-etween examined indicators. The ARDL-PMG results suggest a statistical positive relationship between pollutant emissions and urbanization, electricity consumption and non-renewable energy consumption. Dumitrescu and Hurlin (2012) Granger causality test lends support to the long-run regression results. Bi-directional causality is observed between pollutant emissions, electricity consumption, economic growth and pollutant emissions while a unidirectional causality is apparent between total natural resources rent and pollutant emissions. Based on these results, several policy implications for the African continent were suggested. (a) The need for a paradigm shift from fossil fuel sources to renewables is encouraged in the region (b) The need to embrace carbon storage and capturing techniques to decouple pollutant emissions from economic growth on the continent's growth trajectory. Further policy insights are elucidated.
Keywords: C32; Q40; Q45; 330; non- renewable energy consumption; electricity consumption; economic growth; panel econometrics; Africa